1997
DOI: 10.1103/physrevb.55.10035
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur forming an isoelectronic center in zinc telluride thin films

Abstract: ZnTe 1Ϫx S x epitaxial layers grown on GaAs by molecular-beam epitaxy were studied by photoluminescence ͑PL͒ as a function of temperatures, excitation powers, and hydrostatic pressures. A sulfur-related emission peak, labeled as P 2 , is identified as a deep-level emission by hydrostatic-pressure PL measurement. This indicates that sulfur atoms form isoelectronic centers in a ZnTe matrix. The results qualitatively agree with the theoretical prediction and show experimental evidence of isoelectronic S in ZnTe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…3,4 On the other hand, As and Te atoms can form isoelectronic centers in N-rich GaNAs and S-rich ZnSTe alloys, respectively. [5][6][7][8][9][10] A hole is bound at these centers by a short-range potential resulting from the large difference of electronegativities between S and Te or N and As atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 On the other hand, As and Te atoms can form isoelectronic centers in N-rich GaNAs and S-rich ZnSTe alloys, respectively. [5][6][7][8][9][10] A hole is bound at these centers by a short-range potential resulting from the large difference of electronegativities between S and Te or N and As atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Recent advances of molecular-beam epitaxy ͑MBE͒ technology made the growth of ZnSTe alloys with whole composition possible. 4,5 It then gives the possibility of investigation of the Te isoelectronic centers in the ZnSTe alloys with larger Te composition.…”
Section: Introductionmentioning
confidence: 99%
“…S in ZnS y Te 1Ày (y ¼ 0À0.29) It was predicted [6] that sulfur would form IEC in ZnSTe with a binding energy of about 100-160 meV, however, only a little work [7] devotes to the study of sulfur IEC in ZnSTe. In the following, we have studied the sulfur-related exciton localization in Te-rich ZnSTe alloys.…”
mentioning
confidence: 99%
“…In particular, the isoelectronic doping with oxygen of some II-VI semiconductors has shown that oxygen gives rise to deep traps [35][36][37][38] in which carriers recombine radiatively [39][40][41][42][43]. Cr-doped zinc chalogenides [44][45][46] have been used as broadly tunable continuous wave lasers with negligible non-radiative decay at room temperature.…”
Section: Introductionmentioning
confidence: 99%